(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the current challenges facing the higher education system in the modern labor market and globalization processes - the integration of scientific research and creative activity. The author justifies the importance of creativity and analytical thinking in the training of competitive personnel in the era of developing artificial intelligence and digital technologies. The article highlights the impact of the STEAM approach, project-based learning (PBL) and the use of modern graphic programs in fine arts education on students’ creative potential based on practical examples and international studies. Finally, methodological recommendations are put forward for ensuring the harmony of art and science in higher education, improving the skills of pedagogical staff, and introducing digital technologies.